Penerapan Asas Kebebasan Berkontrak dalam Kontrak Bisnis di Indonesia - Ekacatra Hery Jatmiko (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The principle of freedom of contract is a fundamental tenet in contract law that grants parties the autonomy to determine the content, form, and subjects of an agreement. In the context of business contracts in Indonesia, this principle plays a vital role in providing flexibility for business actors to regulate their legal relationships independently. However, in practice, the implementation of this principle often faces various challenges, such as unequal bargaining power between parties and legal interventions aimed at protecting weaker parties. This study aims to analyze how the principle of freedom of contract is applied in the practice of business contracts in Indonesia, as well as the legal boundaries that limit such freedom. A normative juridical method is employed, using statutory and case study approaches. The findings indicate that contractual freedom in Indonesia is not absolute but is restricted by positive law, propriety, and public order. Therefore, a balance is required between contractual freedom and legal protection in the drafting of business contracts.